3‐2: Analyzing the Degradation Process of Quantum‐Dot LEDs (QLEDs) by Mass Spectometry. Issue 1 (28th June 2022) - Mo, Hin-Wai; Shirakura, Daichi; Harada, Kentaro; Ishibashi, Kiyoshi; Shibamori, Takahiro; Miyamoto, Takashi; Adachi, Chihaya
Abstract : By utilizing time of flight secondary ion mass spectrometry (TOF SIMS), the degradation processes of quantum dot core components and the surface ligands were studied. Intentionally degraded QLED samples were prepared, and the TOF SIMS mass composition signals of each layer within the QLEDs are estimated. The result of the analysis gives possible structural information of the degraded species induced in the device, providing useful insights for further developments of highly efficient R/G/B quantum dot materials.